Análise para implementação de um sistema de controle de manutenção: um estudo de caso - Bandiera, Carlos Tiago (2014)
The industrial sector, since its inception, seeks to maintain in good working order and its conservation tools and machines. The method for accomplishing this task is known as maintenance, however, it is essential that planning and control techniques are aggregated to maintenance. The following work presents a theoretical approach for the implementation of a primary maintenance planning, with implementation in a small food industry. The goal was to design a pre-maintainer sector, poor time by maintenance standards, performance indicators and quality tools applied in this sector. The methodology follows guidance under existing bibliographies, however,changes were made to better adapt to the partner company. After the analysis the results were satisfactory and gave the company a more effective and safe maintenance, corrective maintenance of the index declined, and maintenance performed by outside companies, however, continuity in development of maintenance is needed to increase the quality of maintenance and control.